PURWARUPA HAZARD PINTAR PADA KENDARAAN MPV - Wibowo, Helmi; Sabrina, Sabrina; Srianto, Srianto (Journal of Energy and Electrical Engineering, 2023)
The use of Hazard lights on vehicles is not in accordance with traffic rules so that it often results in accidents. Hazard lights are widely misused and often confuse the driver behind. Based on this, the study made a smart Hazard tool to minimize the number of accidents. The research method used in this study is an experimental method. This smart Hazard makes the Hazard lights turn off automatically without pressing the Hazard light switch when the right and left turn signals are turned on.Â  This tool can be simulated in Multi Purpose Vehicle (MPV) type vehicles with negative controllers and only requires a very small power of 0.398 Watts when the hazard lights are on and the turn signal is on so as not to make the battery consumption large and the voltage considered reasonable so as not to affect other electricity.